PERAN KERJASAMA TIM DALAM PENANGGULANGAN KEBARAN HUTAN DAN LAHAN - Junaidi, Junaidi (Wahana Forestra: Jurnal Kehutanan, 2017)
Land and forest fires (Karlahut) pose a great impact in terms of environment, education, politics, economics, health, inter-state relations and the image of Indonesia in the eyes of the world. As a result of Karlahut has damaged millions of hectares of land and forests that have an impact on material and immate rial losses are very large. Through the Minister of Environment and Forestry of the Republic of Indonesia Number P.32 / MenLHK / Secretariat / Kum.1 / 3/2016 have set a system control forest fires. Teamwork is a critical importance of a system of land and forest fire control. Tampa team that is compact and harmonious then the purpose of the system already built will be difficult to accomplish.